Efficacy of combination terazosin and nifedipine therapy in postoperative treatment of distal ureteral stones after transurethral ureteroscopic lithotripsy. Issue 4 (April 2020) - Ju, Min; Yu, Xiuyue; Wu, Weiwei; Qu, Jingkun; Zheng, Jin
Objective: To investigate the efficacy of combination terazosin and nifedipine therapy in postoperative treatment of distal ureteral stones after transurethral ureteroscopic lithotripsy. Methods: This prospective single-blinded randomized study enrolled 165 patients undergoing transurethral ureteroscopic lithotripsy in our hospital. Patients were randomized into three groups: control, terazosin, and combination treatment (terazosin and nifedipine). Stone discharge rates and times were recorded, along with side effects and complications. Visual Analogue Scale (VAS) score was used to evaluate pain for 7 days postoperatively. International Prostatic Symptoms Score (IPSS) was used to evaluate prostatic function; quality of life (QOL) was evaluated preoperatively and at 7 days postoperatively. Results: The stone discharge rate was significantly higher in the combination group than in other groups; moreover, mean discharge time was shorter in the combination group. Beginning at 3 days postoperatively, VAS scores were dramatically lower in the combination group than in other groups; IPSS and QOL scores were also lower in the combination group. Edema recurrence was significantly less common in combination and terazosin groups than in the control group. Side effects were similar among groups. Conclusion: Combination terazosin and nifedipine therapy was safe and effective in postoperative treatment of distal ureteral stones after transurethral ureteroscopic lithotripsy.